Strategi Digital Public Relations dalam Penyebaran Pesan Dakwah di Kalangan Generasi Z - Miftachul Aula (Bahasa Indonesia, 2026)
Digital transformation has significantly changed the way society accesses and disseminates information, including in Islamic preaching (da’wah) activities. Generation Z, as a cohort that has grown up in the internet era, is closely connected to digital media and tends to access information through various social media platforms. This condition requires communication strategies that are capable of reaching, engaging, and building effective relationships with audiences. One relevant approach is Digital Public Relations, which integrates the use of digital media with the principles of public communication management. This study aims to analyze Digital Public Relations strategies in disseminating da’wah messages among Generation Z. The research employs a qualitative approach using a case study method. Data were collected through observation, interviews, and documentation of digital da’wah activities across various social media platforms. Data analysis was conducted descriptively through the stages of data reduction, data display, and conclusion drawing. The findings indicate that the effectiveness of da’wah message dissemination is influenced by the ability of content managers to present messages that are relevant, engaging, and aligned with the characteristics of Generation Z. The use of communicative language, the utilization of interactive social media features, and consistency in building audience engagement are key factors in enhancing the reach and acceptance of da’wah messages. In addition, communicator credibility and adaptation to the evolving digital platform landscape also contribute to the success of the implemented communication strategies.